2005
DOI: 10.1038/sj.ejcn.1602168
|View full text |Cite
|
Sign up to set email alerts
|

Making healthy choices easy choices: the role of empowerment

Abstract: An important goal of health promotion is to make it easier for people to make healthy choices. However, this may be difficult if people do not feel control over their environment and their personal circumstances. An important concept in relation to this is empowerment. Health professionals are expected to facilitate and enable people moving towards empowerment. In this paper, we address the question what is meant by individual empowerment. In an attempt to provide a theoretical framework, we discuss individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(113 citation statements)
references
References 30 publications
5
107
0
1
Order By: Relevance
“…From its introduction to community psychology in 1981 (Rappaport, 1981), empowerment has become a cornerstone in prevention science and has extended the reach of community psychology to other disciplines such as social work (Itzhaky, 2003) and public health (Koelen & Lindstrom, 2005;Minkler, 2004), as well as to community practice (Holden et al, 2005). In tandem with elaboration of the empowerment construct (Zimmerman, 1990), measurement of PE through the original SPCS (Zimmerman & Zahniser, 1991) was a milestone in the development of empowerment theory.…”
Section: Discussionmentioning
confidence: 99%
“…From its introduction to community psychology in 1981 (Rappaport, 1981), empowerment has become a cornerstone in prevention science and has extended the reach of community psychology to other disciplines such as social work (Itzhaky, 2003) and public health (Koelen & Lindstrom, 2005;Minkler, 2004), as well as to community practice (Holden et al, 2005). In tandem with elaboration of the empowerment construct (Zimmerman, 1990), measurement of PE through the original SPCS (Zimmerman & Zahniser, 1991) was a milestone in the development of empowerment theory.…”
Section: Discussionmentioning
confidence: 99%
“…Basic qualities of the house, like daylight, the level of thermal and sound insulation, and the ease of maintenance are valued for their physical comfort, as well as for providing feelings of privacy, safety, freedom, and independence. A meaningful house enhances feelings of personal control, autonomy, and responsibility, which seem to be pivotal to health development (Koelen & Lindström, 2005) and hence to healthy ageing. People who have a responsibility for day-to-day events, even seemingly small things such as watering plants, or caring for a little bird or dog, have more favourable psychological well-being and show higher health and activity patterns than people without such responsibilities (e.g., Rodin & Langer, 1977).…”
Section: The Communitymentioning
confidence: 99%
“…The title of the fourth Heelsum workshop (2004) (64,(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96) showed that we were aware that empowering and support were needed for both family doctors and patients. The disease-based evidence in primary care, the individual strategy of change, and the population interface of primary care were central themes in this workshop.…”
Section: International Workhops Of the Heelsum Collaboration On Nutrmentioning
confidence: 99%